The right of working women to maternity in Cuba - Jorge Luis Silva González; Sandys Menoya Zayas (Oñati Socio-Legal Series)
Studies related to gender equality in the field of labor relations are of transcendental importance on a global scale. In this sense, this study offers an assessment of the legal protection of the worker's right to motherhood in the forms of management of the Cuban economy, taking into account the constitutional principle of equality and non-discrimination that must govern for all women. Regardless of your employment relationship. For this, with the use of the historical-legal, legal-doctrinal and legal comparison methods, the doctrinal, historical and legal references of the right to maternity are systematized, and its current status in the Corresponding special social security regimes.